Implementation Of Webqual 4.0 For Measuring The Quality Of Baznas.Go.Id Website For User Satisfaction - Nurhadi, Acmad; Yunita, Norma; Mukhayaroh, Anna; Sahirudin, Ahmad (Politeknik Ganesha Medan, 2019)
In general, a government needs a system that can support the process of a service. where service can be interpreted as an effort to take care of what is needed by the community. In this study to measure the quality of the website baznas.go.id by using the webqual 4.0 method. Webqual is a measurement to measure the quality of a website based on research instruments. The research instruments used in webqual 4.0 are usability, information quality, interaction quality, and user satisfaction. The results of this study that the variable information quality (quality information) and usability (usability) have an influence on website users.